A personal dosimeter for smartphones - Choo, Pauline Poh Ling. (2011)
Smartphones are increasingly popular because of their portability and multifunction capabilities, and they are often used as a personal music player by their users-adolescents and adults alike Studies have shown that there is prevalence of hearing damage among smartphone/music player users, particularly adolescents, that excessively listen to music through earphones/headphones. Further, they are at risk of suffering permanent noise-induced hearing loss in later life if they have prolonged exposure to sound/noise exceeding the recommended safe noise dosage. Despite the hearing loss risk, most music player users underestimate the importance of hearing and the dangers of excessive noise exposure, and regularly exceed the safe noise dosage by listening to loud music from their smartphone/music players. Therefore, it is imperative that the smartphone/music player user can be made aware of his/her noise dosage to prevent him/her from exceeding the safe noise dosage.